Analisis Keabsahan Pembebanan Hak Tanggungan Berupa Harta Waris Tanpa Persetujuan Ahli Waris - Aldjufri, Ali Reza; Hazhin, Utiyafina Mardhati (Universitas Jember, 2024)
This study aims to assess the validity of the encumbrance of a mortgage in the form of inherited property without the consent of all heirs. Banks, as financial institutions, have a strategic role in supporting the economic growth of society, including functioning as intermediaries for the interests of parties with excess funds (creditors) and parties who need funds (debtors). Banks provide products to those in need of funds through credit facilities. They usually ask for collateral as a legitimization tool to provide legal certainty to creditors that debtors will carry out their obligations. In reality, however, mistakes or negligence can occur where the certificate is pledged as collateral has the status of inherited property but has yet to be divided. Therefore, the author examines whether the undivided inheritance is valid if pledged without all heirs' consent. This writing is normative research, utilizing a statutory and conceptual approach. The data analysis method used is the descriptive qualitative method. The results of this study show that before providing credit services, banks carefully assess the character, ability, capital, collateral, and business prospects of debtor customers. If the pledged collateral is undivided inherited property, banks require the consent of all heirs. Keywords: Bank, Credit, Inherited Property.